PA composition and preparation method thereof

By introducing specific glow wire performance enhancers and halogen-free phosphorus-containing flame retardants into the PA66 system, combined with zinc borate and phenyl phosphate, the mechanical performance degradation and processing performance problems caused by glow wire performance improvement in the prior art are solved. Comprehensive optimization of high glow wire performance, flame retardant performance and low warpage are achieved.

CN119286249APending Publication Date: 2025-01-10KINGFA SCI & TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411492662.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-10

Smart Images

  • Figure BDA0005100484440000061
    Figure BDA0005100484440000061
  • Figure BDA0005100484440000071
    Figure BDA0005100484440000071
  • Figure BDA0005100484440000072
    Figure BDA0005100484440000072
Patent Text Reader

Abstract

The invention discloses a PA composition and a preparation method thereof, and belongs to the technical field of high polymer materials.A specific glowing filament performance improver is introduced into a PA66 system, meanwhile, a proper flame-retardant system is compounded, the glowing filament performance of a product can be remarkably improved, meanwhile, the flame-retardant performance and mechanical strength are high, the processability is good, and the flame-retardant performance is good. And after processing, the warping degree is low, and the appearance cannot be affected by precipitation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, and in particular to a PA composition and a preparation method thereof. Background Art

[0002] The research and development of electrical devices is inseparable from plastic materials. Among them, polyamide materials are used more frequently in electrical devices than other plastic materials because of their good heat resistance, solvent resistance, high mechanical strength and good processing performance.

[0003] Among polyamide materials, PA66 (nylon 66) has good electrical insulation and excellent heat resistance, but as the use requirements of electrical devices increase, the electrical properties of compounded PA66, such as glow-wire performance, also need to be further improved. In order to improve the glow-wire performance of PA66 in existing processes, special glow-wire performance enhancers or synergists are introduced during product preparation, but this approach may cause other properties of the product, such as mechanical properties, to decline and fail to meet normal use standards, especially under the current trend of halogen-free flame retardant materials. In order to ensure the glow-wire performance and flame retardant performance, the content of the introduced functional additives cannot be too small, and other properties will be more affected.

[0004] In addition, existing flame retardant ingredients, glow-wire performance enhancements or synergists will affect the processing performance of glass fiber reinforced PA66. During processing, the product will have problems such as non-dispersion of components and uneven local shrinkage, which will cause the prepared product to have a large warpage problem. Summary of the invention

[0005] Based on the defects of the prior art, the object of the present invention is to provide a PA composition, which can significantly improve the glow-wire performance of the product by introducing a specific glow-wire performance enhancer into the PA66 system and compounding a suitable flame retardant system, while having high flame retardant performance and mechanical strength, good processing performance, low warpage of the processed product, and no precipitation phenomenon affecting the appearance.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] A PA composition comprising the following components in parts by weight:

[0008] PA66 45-65 parts, glass fiber 15-35 parts, halogen-free phosphorus-containing flame retardant 10-20 parts, zinc borate 1-3 parts, glow-wire performance enhancer A 0.5-3 parts and glow-wire performance enhancer B 0.5-1.5 parts;

[0009] The glow-wire performance enhancer A is at least one of an N-ethyl o-toluenesulfonamide glow-wire performance enhancer, an o-toluenesulfonamide glow-wire performance enhancer, and a p-toluenesulfonamide glow-wire performance enhancer;

[0010] The glow-wire performance enhancer B is phenyl phosphate.

[0011] Preferably, the glow-wire performance enhancer B is at least one of bisphenol A-bis(diphenyl phosphate) and resorcinol tetraphenyl diphosphate.

[0012] In the prior art, in order to improve the electrical performance of the product, a large amount of flame retardant / glowing wire additives and related synergists are generally introduced into PA system products for compounding. However, such an approach, especially when using halogen-free additives, may cause the mechanical strength of the product to be seriously weakened. Moreover, since PA system products generally contain inorganic fillers (such as glass fibers), the component dispersion of the product will inevitably decrease after the introduction of a large amount of functional additives, which may lead to component separation and uneven component dispersion during the processing of the product, uneven processing shrinkage (especially when the product uses glass fibers with large anisotropy as fillers), and the appearance and processing performance are affected. For this reason, in the technical solution of the present invention, on the basis of the glass fiber filled PA66 resin system, a specific high content of halogen-free phosphorus-containing flame retardant is introduced. Compared with the more common halogen-free halogen flame retardant known to the public, it has better stability, will not generate active free radicals during the processing, and has a better degree of dispersion in the PA66 resin, and has a relatively smaller impact on the mechanical strength of the product. However, the flame retardant effect of the halogen-free phosphorus-containing flame retardant is generally low, and its ignition point is low, so the glow-wire performance of the related system products is low. Therefore, the components of the PA composition of the present invention are also compounded with a specific ratio of zinc borate + glow-wire performance enhancer A + glow-wire performance enhancer B. After compounding with the halogen-free phosphorus-containing flame retardant, the four work synergistically, not only can the glow-wire performance of the product be effectively improved, but also the flame retardant performance is relatively high. Since the glow-wire performance enhancer selects specific types of aromatic amides and phenyl phosphates for compounding, they can not only synergistically improve the glow-wire performance of the product, but also have synergistic plasticizing and dispersing functions, inhibiting the decrease in mechanical strength and appearance performance caused by high content of additives, and can also effectively improve the dispersibility of flame retardants and glass fibers in the product during processing, and reduce the warpage of the product.

[0013] Preferably, in the PA composition, the weight percentage of PA66 is within the range of 45 parts, 50 parts, 55 parts, 56 parts, 57 parts, 58 parts, 59 parts, 60 parts, 65 parts or any two of them.

[0014] More preferably, in the PA composition, the weight percentage of PA66 is ≥50wt%.

[0015] Preferably, in the PA composition, the weight of the glass fiber is 15 parts, 20 parts, 25 parts, 30 parts, 35 parts or any two of the range values, the weight of the halogen-free phosphorus-containing flame retardant is 10 parts, 12 parts, 14 parts, 16 parts, 18 parts, 20 parts or any two of the range values, the weight of the zinc borate is 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts or any two of the range values, and the weight of the glow-wire performance enhancer is 0.5 parts, 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts or any two of the range values.

[0016] More preferably, the PA composition comprises the following components in parts by weight:

[0017] 50-60 parts of PA66, 20-30 parts of glass fiber, 12-18 parts of halogen-free phosphorus-containing flame retardant, 1.5-2.5 parts of zinc borate and 1-2 parts of glow-wire performance enhancer.

[0018] Preferably, in the components of the PA composition, the weight ratio of PA66 to the glow-wire performance enhancer A is (119:1) to (19:1).

[0019] More preferably, the weight ratio of the PA66 to the glow-wire performance enhancer is (59:1) to (29:1).

[0020] When the two kinds of aromatic amides specifically defined in the present invention are used as glow-wire performance enhancers, they can not only further accelerate the carbonization rate of the product, thereby synergistically improving the glow-wire performance of the product, but also, at the aforementioned addition amount, can also improve the dispersion effect of the product components and play a certain plasticizing role in the product. When selected within the aforementioned preferred range, the product can achieve better mechanical strength, glow-wire performance and appearance performance.

[0021] Preferably, the viscosity of the PA66 at 23° C. is 2.1 to 3.8 according to ISO 307-2007.

[0022] More preferably, the viscosity of the PA66 at 23° C. is 2.4 to 2.7.

[0023] The viscosity of PA66 resin is not only related to the mechanical strength, but also to the dispersion effect of glass fiber and various functional additives in the product. When it is preferably within the above range, the product not only has better mechanical strength, but also no precipitation phenomenon occurs. The additives can also exert better synergy, the glow-wire performance is better, and the processing warpage is lower.

[0024] Preferably, the halogen-free phosphorus-containing flame retardant is at least one of a red phosphorus flame retardant, a diethyl hypophosphite flame retardant, and a melamine polyphosphate flame retardant.

[0025] More preferably, the phosphorus content of the halogen-free phosphorus-containing flame retardant is ≥ 23 wt %.

[0026] Preferably, the red phosphorus flame retardant is a red phosphorus flame retardant masterbatch with an average particle size of 70 to 150 μm.

[0027] Preferably, the average particle size of the diethyl hypophosphite flame retardant is 20 to 50 μm.

[0028] Preferably, the glow-wire performance enhancer is an N-alkylbenzenesulfonamide type glow-wire performance enhancer.

[0029] In existing PA system products, the aromatic amide selected as the glow-wire performance enhancer A of the present invention is generally used as a plasticizer in combination with an inorganic filler to achieve mechanical balance. However, the inventors of the technical solution of the present invention unexpectedly discovered that when a specific type of aromatic amide is used as a component in a high-content phosphorus-containing flame retardant system, it can not only take into account the plasticizing effect, but also has the effect of synergistically improving the glow-wire performance of the product. Among them, the use of N-alkylbenzenesulfonamide glow-wire performance enhancers has a better effect on improving the mechanical strength, processing performance and appearance performance of the product.

[0030] More preferably, the components of the polycarbonate further include at least one of 0.01 to 1 part of an antioxidant, 0.01 to 1 part of a light stabilizer, 0.01 to 1 part of an ultraviolet absorber, 0.01 to 1 part of a lubricant, and 0.01 to 1 part of a colorant.

[0031] Based on the needs of actual products, technicians in this field can appropriately introduce some components commonly introduced in PA system products without affecting product performance, such as antioxidants, light stabilizers and UV absorbers to improve the aging resistance of products, lubricants to improve product processing performance, and colorants to give products various colors, etc.

[0032] Preferably, the aspect ratio of the glass fiber in the PA composition is 10-70.

[0033] Preferably, the average diameter of the glass fiber is 8-12 μm.

[0034] Preferably, the mesh size of the zinc borate is 400 to 1200 meshes.

[0035] More preferably, the mesh size of the zinc borate is 600-800 mesh.

[0036] It is common knowledge that the main flame retardant and glow-wire performance enhancement mechanisms of zinc borate are heat absorption, oxygen release, formation of a protective layer on the polymer surface, and promotion of carbon layer formation. In the technical solution of the present invention, the inventors have found through experiments that there is a correlation between the mesh size of zinc borate and its dispersibility in the components and the degree of flame retardancy and glow-wire performance enhancement. When the mesh size of zinc borate is selected within the above preferred range, the performance of the product is better.

[0037] Another object of the present invention is to provide a method for preparing the PA composition, comprising the following steps:

[0038] After the components are uniformly mixed, they are melt-extruded and granulated in a screw extruder to obtain the PA composition.

[0039] The preparation method of the PA composition of the present invention has simple operation steps and can realize industrial-scale production.

[0040] Preferably, the temperature range of the screw extruder is set to: 190-270° C., the screw speed is 200-600 r / min, and the screw aspect ratio is 48:1.

[0041] Another object of the present invention is to provide use of the PA composition in preparing electrical devices.

[0042] The PA composition of the present invention has a maximum glow-wire ignition temperature of up to 800° C., and has good flame retardancy, with excellent results in the UL94 standard test. Based on the high dispersibility of the components, the product will not have appearance problems due to component separation, and has high tensile strength, meeting the requirements for device use.

[0043] The beneficial effect of the present invention is that the present invention provides a PA composition and a preparation method thereof, which can significantly improve the glow-wire performance of the product by introducing a specific glow-wire performance enhancer into the PA66 system and compounding a suitable flame retardant system, and at the same time, the flame retardant performance and mechanical strength of the product are high, the processing performance is good, the warpage of the product after processing is low, and no precipitation phenomenon will occur to affect the appearance. DETAILED DESCRIPTION

[0044] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by those of ordinary skill in the art without making creative work premise belong to the protection scope of the present invention. The experimental reagents and instruments involved in the implementation of the present invention, unless otherwise specified, are all commonly used common reagents and instruments.

[0045] Examples 1 to 15

[0046] An embodiment of a PA composition and application thereof according to the present invention, the components of the PA composition are shown in Table 1.

[0047] The preparation method of the PA composition comprises the following steps:

[0048] All the components in the formula are mixed uniformly in a high-speed mixer, and then fed into a twin-screw extruder from a main feeding port for melt blending, extrusion and granulation to obtain the polycarbonate composition.

[0049] When the components are melt-blended and extruded, the temperature zones of the twin-screw extruder are set to 190°C for zone one, 260°C for zone two, 275°C for zone three, 275°C for zone four, 275°C for zone five, 275°C for zone six, 270°C for zone seven, 270°C for zone eight, and 270°C for zone nine, the screw speed is 400rpm, and the screw aspect ratio is 48:1.

[0050] Comparative Examples 1 to 7

[0051] The difference between the comparative examples and the embodiments is only in the types and proportions of components, as shown in Table 2.

[0052] Among the components described in each embodiment and comparative example,

[0053] The PA66-1 is EP122, produced by Huafeng Group Co., Ltd., with a relative viscosity of 2.2 at 23°C;

[0054] The PA66-2 is EPR24, produced by Huafeng Group Co., Ltd., with a relative viscosity of 2.4 at 23°C;

[0055] The PA66-3 is EPR27, produced by Huafeng Group Co., Ltd., with a relative viscosity of 2.7 at 23°C;

[0056] The PA66-4 is T37, produced by Huafeng Group Co., Ltd., with a relative viscosity of 3.7 at 23°C;

[0057] The glass fiber is glass fiber ECS10-03-568H, produced by Jushi Group Co., Ltd., and the glass fiber diameter is 10 μm;

[0058] The halogen-free phosphorus-containing flame retardant 1 is diethyl aluminum hypophosphite, with an average particle size of 35 μm, produced by Jiangsu Liside New Materials Co., Ltd. LFR-8003;

[0059] The halogen-free phosphorus-containing flame retardant 2 is a red phosphorus flame retardant with an average particle size of 100 μm, produced by Tongcheng Xinde New Materials FR9950KF;

[0060] The zinc borate 1 is a commercially available product with a purity of ≥99% and a mesh size of 600 mesh;

[0061] The zinc borate 2 is a commercially available product with a purity of ≥99% and a mesh size of 800 mesh;

[0062] The zinc borate 3 is a commercially available product with a purity of ≥99% and a mesh size of 400 meshes;

[0063] The zinc borate 4 is a commercially available product with a purity of ≥99% and a mesh size of 1200 meshes;

[0064] The glow-wire performance enhancer 1 is an N-alkylbenzenesulfonamide glow-wire performance enhancer, N-butylbenzenesulfonamide, and N-BBSA is produced by Suzhou Jinzhong Chemical;

[0065] The glow-wire performance enhancer 2 is an o-toluenesulfonamide type glow-wire performance enhancer, o-toluenesulfonamide, which is commercially available;

[0066] The glow-wire performance enhancer 3 is bisphenol A-bis(diphenyl phosphate), which is commercially available;

[0067] The glow-wire performance enhancer 4 is p-toluamide, CAS 619-55-6, commercially available;

[0068] The glow-wire performance enhancer 5 is lithium chloride, which is commercially available;

[0069] The glow-wire performance enhancer 6 is melamine polyphosphate MPP, CAS15541-60-3, commercially available;

[0070] The glow-wire performance enhancer 7 is resorcinol tetraphenyl diphosphate, CAS#57583-54-7, which is commercially available.

[0071] Unless otherwise specified, the components and raw materials used in the embodiments and comparative examples of the present invention are all commercially available raw materials, and the components and raw materials used in each parallel experiment are all of the same kind.

[0072] Table 1

[0073]

[0074]

[0075] Table 2

[0076]

[0077] In order to verify the performance of the PA composition of the present invention, the products prepared in each embodiment and comparative example were subjected to the following performance tests, and the specific steps are as follows:

[0078] (1) Glow-wire ignition temperature test: The products of each embodiment and comparative example were injection molded into a sample of size 1.5, and then a glow-wire ignition temperature test was performed according to IEC60695.2-2012;

[0079] (2) 1.5mm flame retardant grade test: tested and determined according to UL94-2023 standard;

[0080] (3) Tensile strength test: The products of each embodiment and comparative example were tested according to ISO527-2012, and the size of the sample strip was 10*4 mm in width.

[0081] (4) Appearance test: Each product was injection molded into a 100*100*2 mm square plate, and the precipitation on the surface of the square plate was observed using a scanning observation instrument. The product was then evaluated for appearance level: Level 1: no precipitation, Level 2: precipitation area less than 5%, Level 3: 5% ≤ precipitation area ratio <15%, Level 4: 15% ≤ precipitation area ratio <30%, Level 5: precipitation area ≥30%;

[0082] (5) Warpage test: Each product is injection molded into a 50*85*2 mm square plate, and then the diagonal warpage value of the square plate is measured. If the warpage value is ≤0.2 mm, the product is judged not to have warpage, otherwise the product is judged to have warpage.

[0083] The test results are shown in Tables 3 and 4.

[0084] Table 3

[0085]

[0086] Table 4

[0087]

[0088] As can be seen from Table 3 and Table 4, the PA composition product of the present invention has ideal comprehensive performance. Not only can the glow-wire ignition temperature reach 750°C and above, up to 800°C, but the flame retardant grade can reach V-0 level, and the tensile strength can reach at least 110MPa, which is practical; the appearance grade of the product can reach level 2 and above, indicating that there is no obvious precipitation phenomenon of each component in the product, the component dispersion is good, and the product does not have obvious warping after processing. In the products of Example 1 and Examples 7 to 9, the viscosity of PA66 used in the products is different. As the viscosity of PA66 increases, the glow-wire ignition temperature and tensile strength of the product change. When the viscosity of PA66 is in the range of 2.4 to 2.7, the comprehensive performance of the product is better. It can be seen from Examples 1 and 11 to 13 that zinc borate in the product of the present invention is a key component for improving the glow-wire performance. Since its main mechanism of action is to absorb heat, release oxygen, form a protective layer on the polymer surface, and promote the formation of a carbon layer, the particle size selected when compounding the components has a certain influence on the performance of the product. After optimization, when the mesh size of zinc borate is 600 to 800 meshes, the glow-wire performance and appearance performance of the product are better.

[0089] In contrast, no zinc borate or glow-wire performance enhancer was introduced into the products of Comparative Examples 1 and 2. The flame retardant of the products not only had a low glow-wire ignition temperature, but also had a flame retardant performance affected. The flame retardant grade of the product of Comparative Example 1 was only V-1, and the product also showed warping. In the product of Comparative Example 3, the addition ratio of the flame retardant and zinc borate was reduced at the same time, and its tensile strength was significantly improved compared with the products of Comparative Example 2 and Example 3, indicating that the introduction of halogen-free phosphorus-containing flame retardant in the product has a greater impact on the mechanical strength of the product, and the strength is higher at a lower content. However, although the mechanical strength of the product is high, its ignition point is too low, the glow-wire ignition temperature is reduced to below 700°C, and the flame retardant performance is significantly reduced, which fully shows that in the product, if the glow-wire performance and flame retardant performance of the product are to be guaranteed, the addition amount of these key components cannot be too small. However, as shown in the product of comparative example 7, when the ratio of matrix resin to glass fiber is certain, if the addition amount of these two components is too much, the glow-wire ignition temperature of the product will not be further increased, but the tensile strength of the product will be reduced, and obvious precipitation will occur, the appearance grade of the product will be reduced to grade 4, and the warpage of the processed product will also be high. Similarly, the total amount of the glow-wire performance enhancer of the present invention and the addition amount of any one of the glow-wire performance enhancers A or B cannot be introduced too much, otherwise, as shown in the product of comparative example 6, comparative examples 10 and 11, the tensile strength, appearance performance and even flame retardant performance of the product will be significantly reduced. In the products of comparative examples 4 and 5, the glow-wire performance enhancer A used is not the type specified by the present invention, the product cannot obtain the expected glow-wire ignition temperature, and it will also affect the appearance performance of the product. At the same time, compared with the product of Example 3, the tensile strength of these two comparative products is also lower, indicating that in the resin system of the present invention, the inappropriate glow-wire performance has a greater impact on the mechanical strength of the product, and the product of comparative example 5 has a high warpage after processing, indicating that conventional lithium chloride cannot play a role in inhibiting the warpage of the product. On the other hand, phenyl phosphate, another glow-wire performance enhancer in the present application, does not only play the flame retardant role required by conventional PA composite products in the present application product, but also cooperates with glow-wire performance enhancer A to enhance the glow-wire performance of the product and plasticize and disperse the product, ultimately ensuring the appearance performance and processing performance of the product. If it is replaced with a flame retardant having a similar flame retardant effect, as shown in Comparative Examples 8 and 9, compared with Example 3, the product of Comparative Example 8 does not add phenyl phosphate, and its weight is supplemented with a halogen-free flame retardant, while the product of Comparative Example 9 replaces phenyl phosphate with MPP with flame retardant activity. The total amount of components with flame retardant activity in the product is the same as that of the product of Example 3. Although the flame retardancy and mechanical properties of the product are not significantly affected, in conventional cognition, the glow-wire performance, appearance performance and processing performance of the product are significantly reduced.

[0090] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A PA composition, characterized in that The composition comprises the following components in parts by weight: PA66 45-65 parts, glass fiber 15-35 parts, halogen-free phosphorus-containing flame retardant 10-20 parts, zinc borate 1-3 parts, glow-wire performance enhancer A 0.5-3 parts and glow-wire enhancer B 0.5-1.5 parts; The glow-wire performance enhancer A is at least one of an N-alkylbenzenesulfonamide glow-wire performance enhancer, an o-toluenesulfonamide glow-wire performance enhancer, and a p-toluenesulfonamide glow-wire performance enhancer; The glow-wire performance enhancement B is phenyl phosphate.

2. The PA composition according to claim 1, characterized in that In the components of the PA composition, the weight ratio of PA66 to the glow-wire performance enhancer A is (119:1) to (19:1).

3. The PA composition according to claim 1, characterized in that The viscosity of the PA66 at 23° C. is 2.1 to 3.8 according to ISO 307-2007.

4. The PA composition according to claim 1, characterized in that The halogen-free phosphorus-containing flame retardant is at least one of a red phosphorus flame retardant, a diethyl hypophosphite flame retardant, and a melamine polyphosphate flame retardant.

5. The PA composition according to claim 1, characterized in that The glow-wire performance enhancer is an N-alkylbenzenesulfonamide type glow-wire performance enhancer.

6. The PA composition according to claim 1, characterized in that The mesh number of the zinc borate is 400 to 1200 meshes.

7. The method for preparing the PA composition according to any one of claims 1 to 6, characterized in that: The following steps are involved: After the components are uniformly mixed, they are melt-extruded and granulated in a screw extruder to obtain the PA composition.

8. Use of the PA composition according to any one of claims 1 to 6 in the preparation of electrical devices.